2008
DOI: 10.1093/humrep/den085
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of human oocytes following in vivo or in vitro maturation

Abstract: Global gene expression profiling using microarrays and bioinformatics analysis has provided a molecular basis for differences in the developmental competence of oocytes matured in vitro compared with in vivo. The over-abundance of transcripts identified in immature germinal vesicle stage oocytes recovered from gonadotrophin stimulated cycles and matured in vitro is probably due to dysregulation in either gene transcription or post-transcriptional modification of genes. Either mechanism would result in an incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 36 publications
9
70
0
6
Order By: Relevance
“…Группа исследователей под руко-водством G. Jones [9] изучала экспрессию генов в оо-цитах, созревших in vivo и in vitro. Ооциты из стиму-лированных циклов по сравнению с естественно со-зревшими ооцитами МII имели различную общую экспрессию генов и соответственно различную ком-петенцию развития.…”
Section: гаметогенез и вртunclassified
“…Группа исследователей под руко-водством G. Jones [9] изучала экспрессию генов в оо-цитах, созревших in vivo и in vitro. Ооциты из стиму-лированных циклов по сравнению с естественно со-зревшими ооцитами МII имели различную общую экспрессию генов и соответственно различную ком-петенцию развития.…”
Section: гаметогенез и вртunclassified
“…In vivo-MII vs IVM-MII In the study by Jones et al, (2008), more than 2000 genes were identified as expressed at more than 2-fold higher levels in oocytes recovered from gonadotropin-stimulated cycles and matured in vitro than those matured in vivo, and 162 of these were expressed at 10-fold or greater levels (this study used Codelink Whole Human Genome Bioarrays, GE Healthcare Biosciences). It was concluded that the overabundance of transcripts in immature oocytes recovered from gonadotropin stimulated cycles, then matured in vitro could be due to dysregulation of either gene transcription or posttranscriptional modifications, resulting in incorrect temporal utilization of genes, culminating in developmental oocyte incompetence.…”
Section: Studies In Human Oocytesmentioning
confidence: 99%
“…Estas técnicas têm sido empregadas em muitos estudos na embriologia (ADJAYE et al, 2007;ARONOW;RICHARDSON;HANDWERGER, 2001;CHEN et al, 2005;DALBIÈS-TRAN;MERMILLOD, 2003;ELLESTAD et al, 2006;FAIR et al, 2007;JEONG et al, 2006;JONES et al, 2008;KATO et al, 2007;MAMO et al, 2006aMAMO et al, , 2006bSIRARD et al, 2005) Na tabela 5 está relacionada a porcentagem de genes incluídos em cada função. O valor ultrapassa 100%, pois alguns genes foram classificados em mais de uma função.…”
Section: Hibridação Das Membranas (Macroarrays)unclassified
“…Contudo, a amplificação de RNA é um método de extrema necessidade em estudos envolvendo quantidades limitadas de amostra, como no caso de embriões bovinos, sendo inviáveis estudos de expressão gênica em larga escala sem a aplicação deste método (ADJAYE et al, 2007;ARONOW;RICHARDSON;HANDWERGER, 2001;CHEN et al, 2005;ELLESTAD et al, 2006;FAIR et al, 2007;GINSBERG, 2005;GOMES et al, 2003;JENSON et al, 2003;JEONG et al, 2006;JONES et al, 2008;KATO et al, 2007;MAMO et al, 2006aMAMO et al, , 2006bMISIRLIOGLU et al, 2006;PATEL et al, 2005;SCHNEIDER et al, 2004;SIRARD et al, 2005;STOYANOVA et al, 2004;ZHU;BABA, 2006). No caso de embriões na fase de AGE, a amplificação do RNA permite análises no momento de menor concentração de RNA, quando estes embriões estão degradando o mRNA materno e iniciando a transcrição do seu próprio genoma.…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation